Managing reality accountability and the miasma of private and public domains - Lehman, Cheryl R. (Bingley, U.K. : Emerald, 2013)
Accounting's contribution to reality construction is envisioned in this volume of critical research, examining accounting's role in contemporary issues: ethics, sustainability, financial instability, post SOX legislation, education, and performance appraisals to name a few. Do CEOs manage rather than reveal environmental liabilities in their never-ending quest for reporting earnings? Under the scrutiny of negative publicity, does the banking community revise images, mask impending crises, and distort regulatory processes? Will shifts in litigation risk influence financial reporting? How do demands and perceptions from powerful external stakeholders change education or organizational processes? How might accounting positively engage in social movements, grass-roots empowerment, and change? These are among the explorations in this volume through case studies, interviews, analysis and interdisciplinary perspectives. Exposing accounting's impact on major social struggles of our times, these works contribute to the debates by revealing that the discipline can be a vital technology in the tool box of governance, political, economic and social practice, holding a key for affirmation and empowerment.
Accountability and performance management systems within private and public sector organisational change processes / Gloria Agyemang, Bill Ryan -- What is fraud in private securities lawsuit? / Nana Y. Amoah -- Litigation risk and management reporting choice : a comparative study of PSLRA and SOX / Meghann Cefaratti ... [et al.] -- Crisis communication in the banking industry : countrywides use of image restoration strategies / Sheri L. Erickson, Mary Stone, Marsha Weber -- Recognizing environmental liabilities surrounding CEO turnovers / Martin Freedman, Jin Dong Park, Jorge Romero -- Social accounting and accounting textbooks : professors responsibility to promote the interests of students / Theresa Hammond, Kenneth Danko, Mark Landis -- An examination of the perceptions of auditors and chief financial officers of various regulations introduced by the DoddFrank financial reform bill / John E. McEnroe, Mark Sullivan -- Commentary and critique of "Sustainability reputation and environmental performance or 'The proof of the pudding is in the eating' by Freedman and Stagliano (2010)" / Fahrettin Okcabol.
Print version record
Keywords: Public finance accounting; Public administration; Accounting -- Social aspects; Industries -- Social aspects; Social accounting; Social responsibility of business